Comparison of clinical indicators between perimenopausal and postmenopausal women with cardiovascular disease - Wang, Jing; Guo, Baolin; Liu, Haifeng; Wang, Zhaoxia; Wang, Rutao; Yin, Tao; Liu, Xiaoqi; Qin, Xing; Yin, Zhiyong (Frontiers in Endocrinology, 2026)
BackgroundCardiovascular disease (CVD) prevalence increases with age, particularly in perimenopausal and postmenopausal women due to declining estrogen levels increasing CVD risk.Methods and resultsFrom 1248 women, 276 with CVD were screened. Clinical indicators (obesity, blood pressure, BMD, hormones) were compared between perimenopausal and postmenopausal women and across age groups (40-44, 45-49, 50-54). Postmenopausal women had significantly higher BMI, WC/HC, BFP, BFD, SBP, DBP, E2, P, PRL (p < 0.001), but lower FSH, LH, BMD T1/T2 (p < 0.001) than perimenopausal women. Significant differences in obesity indicators, BMD, and hormones existed between the 45–49 and 50–54 age groups (p < 0.05).ConclusionsThis study elucidates how hormonal changes affect CVD development in women, providing a basis for early screening and intervention strategies.